Dendritic Cell Plasticity in Tumor-Conditioned Skin: CD14+ Cells at the Cross-Roads of Immune Activation and Suppression - van de Ven, Rieneke; Lindenberg, Jelle J.; Oosterhoff, Dinja; De Gruijl, Tanja D. (Frontiers in Immunology, 2013)
Tumors abuse myeloid plasticity to re-direct dendritic cell (DC) differentiation from T cell stimulatory subsets to immune suppressive subsets that can interfere with antitumor immunity. Lined by a dense network of easily accessible DC the skin is a preferred site for the delivery of DC-targeted vaccines. Various groups have recently been focusing on functional aspects of DC subsets in the skin and how these may be affected by tumor-derived suppressive factors. IL-6, Prostaglandin-E2 and IL-10 were identified as factors in cultures of primary human tumors responsible for the inhibited development and activation of skin DC as well as monocyte-derived DC. IL-10 was found to be uniquely able to convert fully developed DC to immature macrophage-like cells with functional M2 characteristics in a physiologically highly relevant skin explant model in which the phenotypic and functional traits of “crawl-out” DC were studied. Mostly from mouse studies, the JAK2/STAT3 signaling pathway has emerged as a “master switch” of tumor-induced immune suppression. Our lab has additionally identified p38-MAPK as an important signaling element in human DC suppression, and recently validated it as such in ex vivo cultures of single-cell suspensions from melanoma metastases. Through the identification of molecular mechanisms and signaling events that drive myeloid immune suppression in human tumors, more effective DC-targeted cancer vaccines may be designed.